Temporal variability of glucocorticoid receptor activity is functionally important for the therapeutic action of fluoxetine in the hippocampus - Lee, M-S; Kim, Y-H; Park, W-S; Park, O-K; Kwon, S-H; Hong, K. S.; Rhim, H.; Shim, I.; Morita, K.; Wong, D. L.; Patel, P. D.; Lyons, D. M.; et al. (NATURE PUBLISHING GROUP, 2016)
Previous studies have shown inconsistent results regarding the actions of antidepressants on glucocorticoid receptor (GR) signalling. To resolve these inconsistencies, we used a lentiviral-based reporter system to directly monitor rat hippocampal GR activity during stress adaptation. Temporal GR activation was induced significantly by acute stress, as demonstrated by an increase in the intra-individual variability of the acute stress group compared with the variability of the non-stress group. However, the increased intra-individual variability was dampened by exposure to chronic stress, which was partly restored by fluoxetine treatment without affecting glucocorticoid secretion. Immobility in the forced-swim test was negatively correlated with the intra-individual variability, but was not correlated with the quantitative GR activity during fluoxetine therapy; this highlights the temporal variability in the neurobiological links between GR signalling and the therapeutic action of fluoxetine. Furthermore, we demonstrated sequential phosphorylation between GR (S224) and (S232) following fluoxetine treatment, showing a molecular basis for hormone-independent nuclear translocation and transcriptional enhancement. Collectively, these results suggest a neurobiological mechanism by which fluoxetine treatment confers resilience to the chronic stress-mediated attenuation of hypothalamic-pituitary-adrenal axis activity.
Keywords: HEART-RATE-VARIABILITY; GENE-EXPRESSION; ANTIDEPRESSANT DRUGS; STRESS RESPONSES; IN-VIVO; BRAIN; RAT; DEPRESSION; CORTICOSTERONE; ACTIVATION